2018
DOI: 10.1111/ahg.12264
|View full text |Cite
|
Sign up to set email alerts
|

CHRNA3 rs1051730 and CHRNA5 rs16969968 polymorphisms are associated with heavy smoking, lung cancer, and chronic obstructive pulmonary disease in a mexican population

Abstract: CHRNA3/5 polymorphisms are associated with nicotine dependence, LC, and COPD in Mexicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
(32 reference statements)
3
12
0
2
Order By: Relevance
“…Their results support the hypothesis that the T allele may have a protective effect. Importantly, they are in accordance with results from several other studies which show the association of CHRNA3 rs578776 with reduced risk for NA (Bierut et al, 2008) and a protective effect of this SNP against the risk of heavy smoking (Conlon and Bewick, 2011;Pérez-Morales et al, 2018). Another study of Hong and collaborators identified two CHRNA3 variants, namely the rs578776 and rs1051730 (Hong et al, 2010).…”
Section: Current State Of the Art Of The Associations Identified Between Chrna3 Variants Na And Brain Function In Humanssupporting
confidence: 90%
“…Their results support the hypothesis that the T allele may have a protective effect. Importantly, they are in accordance with results from several other studies which show the association of CHRNA3 rs578776 with reduced risk for NA (Bierut et al, 2008) and a protective effect of this SNP against the risk of heavy smoking (Conlon and Bewick, 2011;Pérez-Morales et al, 2018). Another study of Hong and collaborators identified two CHRNA3 variants, namely the rs578776 and rs1051730 (Hong et al, 2010).…”
Section: Current State Of the Art Of The Associations Identified Between Chrna3 Variants Na And Brain Function In Humanssupporting
confidence: 90%
“…Furthermore, Table S1 again shows that a high expression level of α5‐nAChR and survivin is associated with poor prognosis in LUAD samples. Our results are consistent with those of previous studies that demonstrated that α5‐nAChR is likely to be a biomarker of lung carcinogenesis (Le Marchand et al, 2008; Perez‐Morales et al, 2018) and they provide additional evidence of the importance of α5‐nAChR activity in LUAD diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that homomeric α7-nAchR is one of the main nAChR subtype mediating the proliferative and angiogenic effects of nicotine in lung cancer cells (Hajiasgharzadeh et al, 2019;Lyukmanova et al, 2018;Xu et al, 2019). It is worth noting that CHRNA5, encoding α5-nAchR, was highly associated with nicotine-related lung carcinogenesis confirmed by GWAS studies (Kuryatov, Berrettini, & Lindstrom, 2011;Perez-Morales et al, 2018). α5-nAChR has been implicated in nicotine addiction and in determining the number of cigarettes smoked (Sarginson et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…In vitro studies indicate that rs16969968 decreases CHRNA5 function and favors nicotinic addiction [20]. Numerous studies have been performed to find out whether this association is direct, or whether the rs16969968 SNP is simply a proxy for increased exposure to tobacco carcinogens, which were inconclusive [7,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%